Invasive Streptococcus anginosus group infection—does the species predict the outcome? - Junckerstorff, R.; Robinson, James; Murray, R. (Elsevier Ltd, 2014)
Objective - To determine whether there is an association between the species of Streptococcus anginosus group (SAG) bacteria and the clinical outcome. Methods - Isolates from invasive infections caused by SAG bacteria at our institution between January 2004 and February 2009 were identified phenotypically to the taxonomic level of species. Clinical data from the medical records of the patients from whom these isolates were recovered were obtained retrospectively and analyzed. Results - Patients with invasive Streptococcus intermedius infections had a significantly longer hospital stay than patients infected with S. anginosus (p = 0.024) and a significantly higher 30-day all-cause mortality than patients infected with Streptococcus constellatus (p = 0.049). Conclusion - Identification of SAG bacteria to the taxonomic level of species may be of prognostic importance.